2019
DOI: 10.1590/1678-7757-2018-0108
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating clinical and laboratory effects of ozone in non-surgical periodontal treatment: a randomized controlled trial

Abstract: Objective: This study aims to evaluate the clinical and biochemical (oxidative stress and pro-inflammatory mediators) effects of the gaseous ozone use accompanied by scaling and root planning (SRP) in periodontal treatment. Material and Methods: The study population consisted of 40 patients with chronic periodontitis (CP) randomly sorted into two groups of 20. The experimental group received SRP plus 3 watts gaseous ozone in two separate applications five days apart, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 34 publications
1
25
1
3
Order By: Relevance
“…Although there are several studies indicating that topical ozone application with nonsurgical periodontal treatment has no additional benefit in clinical periodontal parameters, 14 , 30 32 few studies have reported significant improvement in periodontal parameters in patients with periodontitis treated with scaling and root planing along with ozone application 15 , 16 . Erdemci, et al 21 (2014) evaluated the effect of SO and TO application after tooth extraction and measured mineralized and trabecular bone and osteoid and osteoblast surfaces for determining alveolar bone healing.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are several studies indicating that topical ozone application with nonsurgical periodontal treatment has no additional benefit in clinical periodontal parameters, 14 , 30 32 few studies have reported significant improvement in periodontal parameters in patients with periodontitis treated with scaling and root planing along with ozone application 15 , 16 . Erdemci, et al 21 (2014) evaluated the effect of SO and TO application after tooth extraction and measured mineralized and trabecular bone and osteoid and osteoblast surfaces for determining alveolar bone healing.…”
Section: Discussionmentioning
confidence: 99%
“…Os níveis glicêmicos dos pacientes já são correlacionados com a saúde e recuperação periodontal, tendo, ambas as doenças, uma correlação estabelecida (Zainal et al, 2021). Dengizek et al, (2019) afirma que o uso do ozônio não foi relevante quando comparado com a raspagem e alisamento coronário, isoladamente. Tal metodologia, no entanto, parece não compreender o uso da terapêutica como medida complementar ao tratamento mecânico.…”
Section: Discussionunclassified
“…Ademais, oito estudos de caráter clínico, também estabeleceram uma relação positiva com a terapia complementar. As formas de aplicação variaram, apresentando-se como nanobolhas (Hayakumo et al, 2013), óleo ozonizado (Nardi et al, 2020, Anzolin et al, 2020; água (R. Niveda, Sankari Malaiappan, 2019, Vasthavi., et al, 2019, Kaur., et al, 2019, Kubyshkina., et al, 2018, Hayakumo., et al, 2012, Srikanth et al, 2013, Ameyaroy., et al, 2021, Huth., et al, 2007, Gusiyska e Kisselova, 2010); e na forma gasosa (Saglam., et al, 2019, Yılmaz., et al, 2013, William C Domb, 2014, Rapone., et al, 2020., Dengizek., et al, 2019.…”
Section: Evaluation Of Salivary Matrix Metalloproteinase (Mmp-8) In Periodontal Patients Undergoing Non-surgical Periodontal Therapy and unclassified
“…This therapeutic intervention applies various anti-inflammatory and antibiotic drugs (e.g. Nonsteroidal anti-inflammatory drug (NSAIDs)), providing better treatment outcomes and less undesirable effects (13). Diacerein, an anthraquinone symptomatic drug, provides high permeability, low solubility and is typically prescribed to treat osteoarthritis, was recently proposed as a potential candidate for the treatment of periodontal diseases (14,15).…”
Section: Introductionmentioning
confidence: 99%